Biomaterial‐Enhanced Cell and Drug Delivery: Lessons Learned in the Cardiac Field and Future Perspectives. Issue 27 (3rd February 2016) - O'Neill, Hugh S.; Gallagher, Laura B.; O'Sullivan, Janice; Whyte, William; Curley, Clive; Dolan, Eimear; Hameed, Aamir; O'Dwyer, Joanne; Payne, Christina; O'Reilly, Daniel; Ruiz‐Hernandez, Eduardo; Roche, Ellen T.; et al.
Abstract : Heart failure is a significant clinical issue. It is the cause of enormous healthcare costs worldwide and results in significant morbidity and mortality. Cardiac regenerative therapy has progressed considerably from clinical and preclinical studies delivering simple suspensions of cells, macromolecule, and small molecules to more advanced delivery methods utilizing biomaterial scaffolds as depots for localized targeted delivery to the damaged and ischemic myocardium. Here, regenerative strategies for cardiac tissue engineering with a focus on advanced delivery strategies and the use of multimodal therapeutic strategies are reviewed. Abstract : Advances in cell and drug delivery platforms comprise the use of a biomaterial depot which can be delivered in a minimally invasive fashion. These materials can be delivered site‐specifically and can permit the controlled release of biotherapeutics in a multimodal fashion.